Travel Literature and the Evolution of the Novel - Adams, Percy G. (Book collections on Project MUSE., 2015)
Although much has been written about how the novel relates to the epic, the drama, or autobiography, no one has clearly analyzed the complex connections between prose fiction as it evolved before 1800 and the literature of travel, which by that date had a long and colorful history. Percy Adams skilfully portrays the emergence of the novel in the fiction of the seventeenth and eighteenth centuries and traces in rich detail the history of travel literature from its beginnings to the time of James Cook, contemporary of Richardson and Fielding. And since the recit de voyage and the novel were then.